Dependence of Properties of Magnetospheric Line Radiation and Quasiperiodic Emissions on Solar Wind Parameters and Geomagnetic Activity. Issue 4 (6th April 2019) - Bezděková, B.; Němec, F.; Parrot, M.; Hajoš, M.; Záhlava, J.; Santolík, O.
Abstract: Very low frequency electromagnetic waves in the inner magnetosphere sometimes exhibit either frequency or time modulation. These phenomena are called, respectively, magnetospheric line radiation (MLR) and quasiperiodic (QP) emissions. Data from Detection of Electro‐Magnetic Emissions Transmitted from Earthquake Regions spacecraft were used to analyze their properties, such as MLR frequency spacing, QP modulation period, and QP intensity as functions of geomagnetic activity and solar wind parameters. Altogether, 1, 152 MLR events and 2, 172 QP emissions were analyzed. It is shown that the influence of the analyzed parameters on QP emissions is different for QP events with modulation periods shorter/longer than 20 s. While the properties of QP events with long modulation periods are significantly related to the geomagnetic activity and solar wind parameters, no such dependences are observed for events with short modulation periods. This suggests that there might be two types of QP emissions generated by two different mechanisms. It is further shown that there seems to be no relation between the properties of QP and MLR events observed at the same times. Finally, the event properties do not seem to be related to the whistler occurrence rate. Key Points: Dependences obtained for quasiperiodic emissions with short/long modulation periods are different Properties of quasiperiodic emissions and magnetospheric line radiation observed at the same times are not related Event properties are not affected by the whistler occurrence